PENDIDIKAN KARAKTER TERINTEGRASI KETERAMPILAN ABAD KE-21 - Zubaidah, Siti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: The 21st Century Skills Integration on Character Education]. Various cases carried out by teenagers require serious handling with a variety of strategies, including through character education. Character education does not mean reducing or replacing